Pengaruh Ekspor, Nilai Tukar Rupiah, dan Penanaman Modal Asing Terhadap Cadangan Devisa Indonesia Tahun 2004-2018 - Nadya Ramadhanty; Ruddy Syafrudin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
The purpose of the study was to determine (1) the effect of exports, the exchange rate of the rupiah, and foreign investment on foreign exchange reserves (2) to determine which variable was the most dominant influence on foreign exchange reserves. Research conducted using multiple linear regression analysis tools, the classic assumption test, stationarity test, f test, t-test, and the coefficient of determination test. The data that has been obtained were analyzed using the E-views version 9 application for processing.      The scope of this research is in Indonesia. Data sources in secondary data were obtained from documentation from relevant agencies related to this study. So it does not require questionnaires or interviews for completeness of data. The variables in this study initially used four (4) independent variables, namely exports, imports, the rupiah exchange rate, and foreign investment, but when testing the assumption constrained by multicollinearity problems until finally this study only used three (3) variables, namely exports, exchange rates, and foreign investment so that the results of the tests are in harmony.       The regression analysis results in this study show that the partial export test has a significant effect and the rupiah exchange rate and foreign investment are not significant. The classic assumption test on normality shows that residuals are normally distributed; in multicollinearity, all variables have no multicollinearity problem, in heteroscedasticity, there is no heteroscedasticity problem, and in autocorrelation, there is no autocorrelation problem. The stationary test shows that all variables are integrated stationary at the second level of differentiation. A simultaneous test of export variables, rupiah exchange rate, and foreign investment simultaneously or together find the results that all significantly affect foreign exchange reserve variables. The most dominant variable influences the foreign exchange reserve variable, namely the export variable